Photonic Jet: Science and Application - Wang, Zengbo; Luk'yanchuk, Boris; Minin, Igor V. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Photonic jets (PJs) are important mesoscale optical phenomena arising from electromagnetic waves interacting with dielectric particles. PJs have applications in super-resolution imaging, sensing, detection, patterning, trapping, manipulation, waveguiding, signal amplification and high-efficiency signal collection, among others. This reprint provides an overview of the field and highlights recent advances and trends in PJ research.